Avalia????o da campanha disputa de condom??nio e sua influ??ncia na redu????o do consumo de ??gua - Silva, Daniela Lima (2014)
Water availability in quantity and quality is a global concern and is demanding actions in terms of planning and management of water resources. Within this context, this research aims to analyze the influence of a campaign to encourage reduced water consumption. The campaign was considered the "Disputa de Condom??nios", promoted by the Sanitation Company of the State of S??o Paulo. Considering the results of the Disputa de Condom??nios campaign was proposed a model for data analysis, which was divided into five steps. In the first step, descriptive statistics, measures of central tendency and dispersion were evaluated (mean and standard deviation) of the data of water consumption in a wider period and subdivided into pre-campaign, engagement, campaign and post-campaign and the results were compared between periods in relation to the stage of dispute. In the second stage, based on models of time series forecasting values obtained during the pre - campaign were used to project trends in consumption and compared with the results actually measured. The third stage used similar to the first and second procedures, but with a control group to verify the influence of the stimulus, Disputa de Condom??nios campaign on consumption. In the fourth stage the influences of temperature variation in consumption were recorded during the same time period analyzed using inferential statistics (correlation and regression). In the fifth step, from the results obtained in the previous steps, was measured consumption reduction that could be assigned as affected by the campaign. As a result, it was found that the campaign had no significant effect on reducing water consumption and also no correlation between water consumption and climate variations in the analyzed period. It was concluded that it takes a broader time scale for assessing trends in water consumption and to exert influence in reducing energy consumption should be more time devoted to engagement and good practice guidance. Moreover, the post- campaign monitoring should be thought of as actually relevant to assess the influence of this type initiative period, since its purpose is continuity.